Etyczne i prawne aspekty dopuszczalności przeprowadzania doświadczeń na zwierzętach - Żukowski, Łukasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Article devoted to the legal and ethical acceptability of scientific researches using animal-based models. Philosophical and legal approach to the issue of animal rights has along history and underwent significant changes. The legal status of animals and the issue of preventing the suffering of the animals are still the subject of social controversy. Against this background, there is adebate on the scope of the necessary regulations. One of them is the issue of animal testing governed by the Law of 21 January 2005 on animal experiments. The solutions adopted in the Act are to reduce animal suffering and to adjust Polish law to the requirements of the European Union law.
Keywords: scientific researches using animal-based models; animal experiments; Polish law; EU law